Short-Term Impact of Plant and Liquid derived Fulvic Acids on the Physiological Characteristics, Plant Growth and Nutrient Uptake of Maize-Wheat Production: Effect of fulvic acid on growth and soil - Sootahar, Mahendar Kumar; Soothar, Mukesh Kumar; Zeng, Xibai; Ye, Ning; Sootahar, Punam; Kumar, Rakesh; Zanour, Abdul Khalique; Soothar, Permanand; Bhangar, Ehsan Elahi; Baloch, Siraj Ahmed; Kumar, Suneel (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2022)
Fulvic acids (FAs) are the major component of soil organic matter, which improves soil structure and fertility. FA has been observed positively on plant growth and ultimately enhances crop production. The pot experiment was conducted on wheat and maize grown in silty clay, sandy loam, and clay loam textural soils, respectively. Three different parent materials; FA Solid (S=Powder Form), Natural Liquid (NL) and Plant-derived Liquid (P) were applied at 0% (Control), 0.25 % (S), 0.50 % (NL) and 0.50 % (P) FA, respectively. The results showed that the stem diameter of maize was 15.68, 26.90, and 26.35 mm under S, P, and NL respectively, however, the spike weight of wheat was 123.24, 98.5, and 132.4 g pot-1 for S, P, and NL in Albic (AL), Irrigated Desert (IR) and Shahjiang (SH) soils. Similarly, maize height increased by 8 % and 9 % significantly as compared to control and the height of wheat increased by 4 % and 1 % in AL and 5 % in IR soil compared to control. Maize grain weight increased over control; however, wheat grain weight significantly decreased. The N and P significantly enhanced in maize and wheat in AL, IR, and SH soils. Our study proved that the application of Solid FA did not improve maize growth characteristics, however, it improved the characteristics of wheat crops except under IR soils. In contrast, liquid FA improved the chemical and physical properties of soils including nutrient uptake of maize and wheat under AL and SH soils.